The Evolution of Vigilance and Its Atrophy Preceding the COVID-19 Global Pandemic - Witek, Theodore J.; Schwartz, Robert (Frontiers in Public Health, 2022)
Introduction Recent infectious outbreaks preceding the COVID-19 crisis resulted in the evolution of vigilance for preparedness against the next pandemic. This vigilance was maintained to varying degrees in different jurisdictions. Objective To evaluate the evolution of vigilance following previous epidemics and pandemics and the subsequent atrophy of vigilance prior to the COVID-19 global pandemic. Methods We evaluated documentation discussing US, Canada, and South Korea from March 2002 to October 2021. Our policy search strategy was rooted in academic literature, government documents and media reports. Results In the US, there were examples of atrophy of vigilance; however, there was clear understanding of pandemic readiness actions that were simply not executed amongst political chaos. In Canada, political mishaps were less evident at the time the pandemic unfolded. Nevertheless, atrophy was evident with erosion in preparedness programs following SARS. South Korea appeared least subjected to atrophy of vigilance. The more recent MERS outbreak prompted evolution of sustained vigilance and compliance with basic public health measures such as mask wearing. Recommendations Policy options need to be explored and instituted that increase protection of preparedness programs through institutional safeguards and accountability measure.